تطوير مادة كتاب المتممة الأجرومية على أساس خريطة المفاهيم لترقية كفاءة الطالبات في علم النحو بمعهد سبيل الرشاد السلفى مالانج - Diana, Zahara Ulya; Jauhari, Qomi' Akit (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
ABSTRACT Not Nahwu material is the ultimate goal in learning, but requires media in achieving goals. Media in learning is very important for the students in Nahwu material. In order for teachers to deliver Nahwu material attractively and effectively, media is needed. Researchers take one of the media that is in accordance with this study, namely the concept of thinking (concept map). The formulation of the problem in this study is: (1) How is the development of the book Mutamminah Al-Ajrumiyah complementary to nahwu subjects based on the, concept map at the Diniyyah level at the Sabilurrasyad Salafi Malang Islamic Boarding School? (2) How effective is the use of textbooks for, concept map based Nahwu material at the early level at the Sabilurrasyad Salafi Malang Islamic Boarding School? This research uses Research and Development method. The development model used is the ADDIE model which has 5 stages of research and development. The data collection techniques used are tests (pretest and post test), interviews, test questionnaires of validators of media experts and material experts, and user response questionnaires. Meanwhile, to analyze data related to the effectiveness of the use of electronic modules, researchers use the N-Gain formula. The results shows: (1) the development of the book Mutamamah al-Ajrumiyah then developed into the